2021
DOI: 10.1155/2021/6685840
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of High-Risk Missense Variants in Human ACE2 Gene and Susceptibility to SARS-CoV-2 Infection

Abstract: SARS-CoV-2 coronavirus uses for entry to human host cells a SARS-CoV receptor of the angiotensin-converting enzyme (ACE2) that catalyzes the conversion of angiotensin II into angiotensin (1-7). To understand the effect of ACE2 missense variants on protein structure, stability, and function, various bioinformatics tools were used including SIFT, PANTHER, PROVEAN, PolyPhen2.0, I. Mutant Suite, MUpro, SWISS-MODEL, Project HOPE, ModPred, QMEAN, ConSurf, and STRING. All twelve ACE2 nsSNPs were analyzed. Six ACE2 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“… 1 , 2 , 3 Fever, sputum production, fatigue, shortness of breath, and cough are the most frequent SARS‐CoV‐2 symptoms. 3 , 4 , 5 , 6 The establishment of SARS‐CoV‐2 disease relies on a particular interplay between Spike glycoprotein and angiotensin‐converting enzyme 2 (ACE2) (from the host). 7 , 8 , 9 The viral spike protein priming is carried out by the cellular serine protease transmembrane protease serine 2 (TMPRSS2), a cleavage that promotes the fusing of membranes (between viral and cellular membranes) viral propagation in the cells infected with SARS‐CoV‐2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 , 3 Fever, sputum production, fatigue, shortness of breath, and cough are the most frequent SARS‐CoV‐2 symptoms. 3 , 4 , 5 , 6 The establishment of SARS‐CoV‐2 disease relies on a particular interplay between Spike glycoprotein and angiotensin‐converting enzyme 2 (ACE2) (from the host). 7 , 8 , 9 The viral spike protein priming is carried out by the cellular serine protease transmembrane protease serine 2 (TMPRSS2), a cleavage that promotes the fusing of membranes (between viral and cellular membranes) viral propagation in the cells infected with SARS‐CoV‐2.…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19, a novel infectious disease discovered in China in December 2019, is triggered by SARS‐CoV‐2, a highly emerging deadly pathogen 1–3 . Fever, sputum production, fatigue, shortness of breath, and cough are the most frequent SARS‐CoV‐2 symptoms 3–6 . The establishment of SARS‐CoV‐2 disease relies on a particular interplay between Spike glycoprotein and angiotensin‐converting enzyme 2 (ACE2) (from the host) 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variations in the host ACE2 receptor may also influence the susceptibility or resistance to the SARS-CoVs. Several in silico studies suggested that ACE2 SNVs might affect the binding affinity to the S protein ( 15 , 23 , 24 ). However, only a few studies have reported on the biological importance of ACE2 SNVs in the cellular entry of SARS-CoVs ( 16 , 25 , 26 ), and the information on this topic is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Initially we choose six SNPs rs17852044, rs41305781, rs41310789, rs74440199, rs76519302, rs199725032 to select the most deleterious nsSNPs and to increase the precision of the analysis.Among these six, only one missense variant that is rs41310789, was found to be most pathogenic. This predicted nsSNPs were both causing epilepsy syndrome, focal epilepsy, and certain CNS disorders or cognitive diseases.Moreover, a wet lab molecular and functional analysis is necessary further to elucidate these nsSNPs in epilepsy and its related disorders [36][37][38].…”
Section: Graphical Abstract Conclusionmentioning
confidence: 99%